N03 Prenatal diagnosis for Huntington's disease: a generation of testing. (29th August 2012) - Miezybrodzka, Z; Rae, D; Matheson, K; Glew, R; Lashwood, A; Simpson, S; ,
Abstract : Background: The UK Huntington's disease (HD) predictive testing consortium was formed to monitor trends in clinical practice in the UK. Tests for HD serve as a paradigm for predictive and prenatal diagnosis (PND) in as yet untreatable disorders. Aim: To describe uptake of PND for HD from the start of testing in 1994 to date. Method: An annual survey of UK genetics centre clinicians was performed to gather anonymised data on patient characteristics and outcomes. Results/outcome: Our dataset now describes the behaviour of a generation at risk- those facing PND choices today are often the offspring of parents who had the opportunity themselves to test a pregnancy. Although most of those at risk of HD choose not to test pregnancies, prenatal diagnosis remains an important option not only to those who know they carry the gene, but also to those at 50% risk who choose to remain untested. Direct PND remains more popular than exclusion PND. Intriguingly, numbers of direct prenatal diagnostic tests in the UK (population 5.5 million) have fallen over time, from around 20 per year to around 10, whereas numbers of prenatal exclusion tests have remained similar at around 5. This fall in number of direct prenatal diagnoses performed is similar to the number of those undergoing pre-implantation genetic diagnosis in the UK for HD each year. Female partners of men at risk of HD make 2/3 of the test requests. Conclusion: 28 years on, prenatal diagnosis remains an important option for a small group of those at risk. However, increasing numbers of patients are choosing pre-implantation genetic diagnosis, either by direct or exclusion methods. Despite increased optimism in the HD community, not only direct PND but also exclusion PND remains an important option for those at risk.